Numerical investigation of the potential of using hydrogen as an alternative fuel in an industrial burner - Rashed Al-ajmi (19932174) (2024)
This study investigates hydrogen and hydrogen-methane mixtures as alternative fuels for industrial burners, focusing on combustion dynamics, flame stability, and emissions. CFD simulations in ANSYS Fluent utilized the RANS framework with the k-ε turbulence model and the mixture fraction/PDF approach. Supporting Python scripts and Cantera-based kinetic modeling employing the GRI-Mech 3.0 mechanism and Zeldovich pathways analyzed equivalence ratios (Φ), adiabatic flame temperatures (Tad ), and NOx formation mechanisms. Results revealed non-linear temperature trends, with a 50% hydrogen blend yielding the lowest peak temperature (1880 K) and a 75% hydrogen blend achieving optimal performance, balancing peak temperatures (∼1900 K), reduced NOx emissions (5.39 × 10-6), and near-zero CO2 emissions (0.137), though flame stability was impacted by rich mixtures. Pure hydrogen combustion produced the highest peak temperature (2080 K) and NOx emissions (3.82 × 10-5), highlighting the need for NOx mitigation strategies. Mass flow rate (MFR) adjustments and excess air variation significantly influenced emissions, with a 25% MFR increase reducing NOx to 2.8 × 10-5, while higher excess air (e.g.,30%) raised NOx under lean conditions. Statistical analysis identified Φ, hydrogen content (H2%), and flame stability as key factors, with 50%–75% hydrogen blends minimizing emissions and optimizing performance, emphasizing hydrogen’s potential with controlled MFR and air adjustments. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2024.134194